Screening for acute childhood malnutrition during the National Nutrition Week in mali increases treatment referrals. - Daniele H Nyirandutiye; Akory Ag Iknane; Amadou Fofana; Kenneth H Brown (PLoS ONE, 2011)
OBJECTIVE: To evaluate a pilot intervention designed to integrate mid-upper arm circumference (MUAC) screening for acute malnutrition into the semi-annual Child Nutrition Week (Semaine d'Intensification des Activités de Nutrition, or "SIAN") activities carried out in June 2008. DESIGN: A cross-sectional survey was conducted in Kolokani and Nara, two health districts in the Koulikoro region of Mali, 4-5 months after the SIAN, using a population-proportionate, multi-stage random sample of: 1) health centers, and 2) households in communities linked to each of the selected health centers. Caregivers of 1543 children who were 6-59 months of age at the time of the SIAN, 17 community-based volunteers and 45 health center staff members were interviewed. RESULTS: A total of 1278 children 6-59 months (83% of those studied) reportedly participated in SIAN. Of the participating children, 1258 received vitamin A (98% of SIAN participants; 82% of all eligible children), 945 received anti-helminth tablets (84% of participants; 71% of eligibles), and 669 were screened for acute malnutrition (52% of participants; 43% of eligibles). 186 of the children screened (27%) were reportedly identified as acutely malnourished. SIAN screening covered a significantly greater proportion of children than were examined in both community-based (22% of children) and health center-based screening activities (5% of children) combined during the 4-5 months after the SIAN (P<0.0001). In general, community volunteers and health personnel positively evaluated their experience adding MUAC screening to SIAN. CONCLUSION: Integrating MUAC screening for acute malnutrition in SIAN permits the assessment of a large number of children for acute malnutrition, and should be continued.